Improving mental health literacy among young people aged 11-15 years in Java, Indonesia: the co-development of a culturally-appropriate, user-centred resource (The IMPeTUs Intervention) - Helen Brooks; Armaji Kamaludi Syarif; Rebecca Pedley; Irman Irmansyah; Benny Prawira; Karina Lovell; Cicih Opitasari; Adam Ardisasmita; Ira Savitri Tanjung; Laoise Renwick; Soraya Salim; Penny Bee (BMC, 2021)
Abstract Background Many mental health problems emerge in late childhood and contribute significantly to the global burden of disease. Adverse outcomes can extend into adulthood if left untreated. This impact is exacerbated in low- and middle-income countries where significant treatment gaps persist. Improving mental health literacy may offer an effective strategy for early intervention but remains underexplored in these contexts. Methods An intervention was co-developed with children and young people (CYP) by undertaking a needs analysis combined with stakeholder consensus activities. A systematic review of mental health literacy interventions in South-East Asia was undertaken in addition to semi-structured interviews with 43 children and young people (19 with and 24 without experience of anxiety and depression), 19 parents of children with experience of mental health problems and 25 education and health professionals. A focus group was also held with 8 key stakeholders immersed nationally in policy and practice. Interview schedules explored participants' experiences of mental health, unmet needs and priorities for intervention. Data were synthesised and presented at a 3-day co-production workshop. Attendees included 13 CYP, 6 parents/guardians, 2 teachers, 8 health professionals, 2 academics and 3 game designers. Consensus exercises were utilised to identify the preferred format, content and delivery of the intervention. A smaller group of patient and public involvement contributors worked with designers to further iterate the intervention. Results An immersive storyline digital application was co-developed for young people aged 11-15 with the primary aim of improving mental health literacy and self-management. The intervention comprises two chapters; one depression focussed, and the other anxiety focussed. The storyline format is interspersed with interactive games and exercises to promote engagement and encourage self-management. CYP also take part in group sessions delivered by trained facilitators before and after intervention use to discuss outcomes of and issues raised during the game. Conclusion The IMPeTUs intervention has been co-designed for CYP aged 11-15 to improve mental health literacy and enhance self-management abilities. To the best of our knowledge, this is the first Indonesian digital intervention to improve mental health literacy and self-management for this population. Implementation, acceptability, and impact are currently being explored in a multi-site case study evaluation.